Application of ZIF-8 wrapped hemoglobin composite material in preparation of lithium-sulfur battery

The in-situ biomineralization method encapsulates hemoglobin in ZIF-8, which solves the problem of electrolyte destroying the enzyme structure and improves the performance of lithium-sulfur batteries.

CN119650697AInactive Publication Date: 2025-03-18Wenzhou University Carbon Materials and Hydrogen Energy Industry Technology Research Institute

Patent Information

Application Number
CN202510059795.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, when hemoglobin is directly added to the lithium sulfur battery, the electrolyte in the battery will destroy the structure of the enzyme, resulting in poor battery performance.

Method used

Through in situ biomineralization method, hemoglobin is encapsulated in ZIF-8 to form a ZIF-8-encapsulated hemoglobin composite material, which is used for the preparation of lithium-sulfur batteries. The method is carried out under mild conditions without destroying the enzyme structure.

Benefits of technology

The MOF@ enzyme complex prepared by this method preserves the inherent structure of the enzyme and improves the electrochemical and kinetic properties of lithium-sulfur batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650697A_ABST
    Figure CN119650697A_ABST
Patent Text Reader

Abstract

According to the application of the ZIF-8 coated hemoglobin composite material in preparation of the lithium-sulfur battery, an enzyme solution, an organic ligand and metal ions are co-precipitated through in-situ biomineralization to prepare an MOF-enzyme compound, the method is not influenced by the size of enzyme molecules, the synthesis condition of ZIF-8 is mild, the structure of enzyme cannot be damaged in the reaction process, and the preparation method is simple and easy to implement. And the synthesis process has the advantages of short reaction time, no need of other organic solvents, capability of expanding multiple synthesis, simple synthesis method and high yield. The results of XRD, FIIR and XPS experiments show that the MOF (at) enzyme compound prepared by the method preserves the inherent structure of the enzyme, and when the MOF (at) enzyme compound is assembled into a battery, the electrochemical performance and the dynamic performance of the battery containing ZIF-8 (at) Hb are better.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium-sulfur battery preparation, and in particular to application of a ZIF-8-wrapped hemoglobin composite material in the preparation of a lithium-sulfur battery. Background Art

[0002] Scientists from the University of Cordoba and the Polytechnic University of Cartagena in Spain have developed a new type of battery. The battery uses hemoglobin as a catalyst for electrochemical reactions, is biocompatible, and can operate for 20 to 30 days. Taking the zinc-air battery as an example, when air enters the battery, hemoglobin reduces oxygen at the cathode of the battery and converts it into water, releasing electrons. These electrons migrate to the anode of the battery, oxidizing zinc.

[0003] The applicant discovered that if hemoglobin is added directly to a lithium-sulfur battery, the electrolyte in the battery will destroy the structure of the enzyme, resulting in poor performance.

[0004] In the past few decades, enzymes have been widely accepted for their ease of production, substrate specificity and selectivity, and environmental friendliness. However, the inherent disadvantages of enzymes, such as sensitivity to temperature, pH, ionic strength, and other conditions, are easy to inactivate or lose catalytic activity, which hinders the practical use of enzymes. Enzyme immobilization is the most powerful way to overcome these disadvantages. The immobilization strategy can significantly improve the performance of enzymes. This method mainly prevents subunit dissociation through multi-subunit immobilization, prevents protease aggregation, autolysis or proteolysis, rigidifies the enzyme structure through multi-point covalent connection, and generates a favorable microenvironment. In contrast, improving selectivity through immobilization can be summarized as follows: changing the geometry of the active center through immobilization, stabilizing the enzyme conformation, and eliminating diffusion limitations. Some nanomaterials, such as nanoparticles and metal-organic frameworks (MOFs), have been used as new carriers for enzyme immobilization because of their larger specific surface area and less diffusion limitations. However, since traditional nanomaterials are often prepared under harsh conditions, the process of enzyme fixation will indirectly lead to low protein loading efficiency and severe reduction in enzyme activity. Many MOFs can be prepared under mild conditions, so MOFs are very suitable for stabilizing the conformation of enzymes through specific host-guest interactions and / or confinement effects.

[0005] The researchers found that MOF@enzyme can be used for enzyme immobilization in four ways: 1) Immobilization by physical adsorption. Enzymes can be immobilized on the carrier through weak interactions (such as hydrogen bonds, electrostatic interactions, van der Waals forces, etc.). Since physical adsorption is a weak binding, although it does not change the natural structure of the enzyme, a weak stable bond is formed between the enzyme and the MOF. The enzyme will fall off during this process, which will also lead to performance inactivation.

[0006] 2) Fixation by covalent bonds. Some functional groups on the surface of the enzyme can be covalently fixed to the groups in the MOF. This method is conducive to maintaining the reactivity of the group and the flexibility of the enzyme molecule, but a cross-linking agent is required during the reaction to enhance the attachment to the carrier, which may change the spatial conformation of the enzyme and affect the catalytic activity of the enzyme.

[0007] 3) Pore encapsulation. Confining enzymes in 3D microenvironments can improve stability and minimize protein unfolding. However, for macromolecular substrates, nano / mesoporous MOFs may hinder the accessibility of captured enzymes, and thus the mass transfer efficiency of substrates may be severely limited.

[0008] 4) Co-precipitation strategy (also known as biomineralization). Nucleation and growth of MOF formation and enzyme immobilization occur simultaneously in one step. Encapsulation of enzymes by a “precipitation” approach. The tight MOF coating acts as a protective shell, preventing enzyme leaching and conformational changes. Summary of the invention

[0009] The present invention aims to provide application of ZIF-8 encapsulated hemoglobin composite material in preparation of lithium-sulfur battery.

[0010] To achieve the above object, the present invention provides the use of a ZIF-8-wrapped hemoglobin composite material in the preparation of a lithium-sulfur battery.

[0011] Preferably, the ZIF-8 encapsulated hemoglobin composite material is prepared by the following method: firstly, a 2-methylimidazole methanol solution is mixed with a hemoglobin aqueous solution to obtain a mixed solution, then a zinc nitrate methanol solution is added to the mixed solution, ultrasonically vibrated, stirred at room temperature, centrifuged to obtain a precipitate, washed, and dried to obtain the obtained product.

[0012] Further preferably, the volume ratio of 2-methylimidazole methanol solution, hemoglobin aqueous solution, and zinc nitrate methanol solution is 9:1:10, the concentration of 2-methylimidazole methanol solution is 0.030-0.040 g / mL, the concentration of hemoglobin aqueous solution is 55-65 mg / mL, and the concentration of zinc nitrate methanol solution is 0.025-0.03 g / mL.

[0013] More preferably, the concentration of the 2-methylimidazole methanol solution is 0.035 g / mL, the concentration of the hemoglobin aqueous solution is 60 mg / mL, and the concentration of the zinc nitrate methanol solution is 0.0275 g / mL.

[0014] Further preferably, the process conditions of the ultrasonic oscillation treatment are: 500W ultrasonic oscillation for 30 minutes.

[0015] Further preferably, the process condition of stirring at room temperature is: stirring at 600 r / min for 24 hours.

[0016] Further preferably, the centrifugal process conditions are: 8000r / min for 3min, and centrifugation for 5 times.

[0017] More preferably, washing with methanol is performed three times until the upper layer liquid is clear and colorless.

[0018] Further preferably, the drying process conditions are: drying at 60° C. for 12 hours.

[0019] The present invention has the following beneficial effects: The present invention provides the application of ZIF-8 encapsulated hemoglobin composite material in the preparation of lithium-sulfur battery. Since the pore size of most MOFs reported so far is smaller than the size of enzymes, for the encapsulation of large enzymes such as hemoglobin, the present invention prepares MOF@enzyme complex by co-precipitation of enzyme solution, organic ligand and metal ions through in-situ biomineralization. This method is not affected by the size of the enzyme molecule itself, and the synthesis conditions of ZIF-8 are mild, and the structure of the enzyme will not be destroyed during the reaction. In addition, the reaction time of the synthesis process is short, no other organic solvents are required, and the synthesis can be expanded multiple times. The synthesis method is simple and has a large yield. The experimental results of XRD, FIIR and XPS show that the MOF@enzyme complex prepared by this method preserves the inherent structure of the enzyme, and it is assembled into a battery. It is found that the battery containing ZIF-8@Hb has better electrochemical performance and kinetic performance.

[0020] In addition to the above-described purposes, features and advantages, the present invention has other purposes, features and advantages. The present invention will be further described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings: Figure 1 . Images of hemoglobin, ZIF-8, and ZIF-8@Hb.

[0022] Figure 2 . Morphological characterization: SEM images of ZIF-8 (a) and ZIF-8@Hb (b).

[0023] Figure 3 . XRD of ZIF-8 and ZIF-8@Hb picture (a) and FTIR graph (b).

[0024] Figure 4 . Rate performance of batteries containing different contents of ZIF-8@Hb cathode.

[0025] Figure 5.Excellent electrochemical performance, including (a) rate performance of CNT, ZIF-8 and ZIF-8@Hb batteries at 0.2, 0.5, 1.0, 2.0, 3.0 and 5.0 C, respectively; (b) representative voltage-capacity curves of ZIF-8@Hb at 0.2, 0.5, 1.0, 2.0, 3.0 and 5.0 C; (c) voltage-capacity curves of different electrodes at 3.0 C; (d) E / S ratio of 5 μL mg −1 and 5.0 mg cm −2 Cycling performance of ZIF-8@Hb batteries at 0.1 and 0.2 C under high sulfur loading.

[0026] Figure 6 . Charge and discharge platform curves of ZIF-8 (a) and CNT (b) at different rates.

[0027] Figure 7 . Galvanostatic charge / discharge curves of ZIF-8@Hb, ZIF-8, and CNT cathodes at (a) 0.2 C, (b) 1.0 C, (c) 2.0 C, and (d) 5.0 C in the second cycle.

[0028] Figure 8 . Long cycling performance of ZIF-8@Hb, ZIF-8 and CNT batteries at 3.0 C high rate. DETAILED DESCRIPTION

[0029] The embodiments of the present invention are described in detail below with reference to the accompanying drawings, but the present invention can be implemented in many different ways as defined and covered by the claims.

[0030] Example 1.1 Material preparation (1) Preparation of ZIF-8 and ZIF-8@Hb materials First, prepare 9 ml of a methanol solution containing 2-methylimidazole (0.308 g) and 1 ml of H 2 O or 1 ml Hb (hemoglobin) aqueous solution (60 mg / mL). Then add 0.279 g Zn(NO 3 ) 2 6H 2 O methanol solution 10 mL, put it into the ultrasonic machine for half an hour. Then, after vigorous stirring at room temperature for 24 hours, the mixed solution was centrifuged 3 times and washed with methanol 3 times until the upper liquid was clear and colorless. The collected solid was placed in a vacuum oven and dried at 60 ° C for 12 hours to obtain ZIF-8 and ZIF-8@Hb.

[0031] (2) Preparation of carbon / sulfur composites The C / S composite material was prepared using the conventional melt diffusion method. The purchased high-purity sulfur and carbon nanotubes were mixed in a mass ratio of 7:3 and ground for half an hour. The C / S composite material was then treated in a vacuum oven at 155°C for 12 hours, cooled to room temperature, and re-ground to obtain a smaller C / S composite material with a sulfur content of ~70 wt%. The subsequent high sulfur loading was performed by mixing high-purity sulfur and carbon nanotubes in a mass ratio of 9:1 and grinding for 1 hour, and the subsequent steps were the same as above.

[0032] 1.2 Material characterization The crystal structures of ZIF-8 and ZIF-8@Hb were characterized using a Bruker D8 FOCUS polycrystalline powder X-ray diffractometer with a measurement range of 10 to 80 degrees in the 2θ range. The morphology and structure of the materials were characterized using a scanning electron microscope (JSM-6700F). The chemical state was analyzed by X-ray photoelectron spectroscopy (XPS) using a PHI 5000 VersaProbe III and an Al Kα source. The ultraviolet-visible (UV-Vis) absorption spectra were recorded using a Cary 60 UV-Vis spectrophotometer. The chemical microenvironment of Hb incorporated into ZIF-8 was studied using a Fourier transform infrared spectrometer (iS50, Thermo Fisher).

[0033] 1.3 Battery assembly and electrochemical measurements The carbon / sulfur composite material, polyvinylidene fluoride (PVDF), conductive additive (CNT, carbon nanotube) and ZIF-8@Hb were mixed in a mass ratio of 80:5:14.5:0.5 and placed in an ultrasonic machine for 1 hour. Then it was placed on a stirrer and stirred continuously for 14 hours to produce a uniform slurry. Aluminum foil was used as a current collector, and the slurry was evenly coated on it with a coater. Then it was placed in a vacuum oven and dried at 60°C for 12 hours to completely remove the nitrogen methyl pyrrolidone (NMP) solvent. Finally, the dried sample was cut into discs with a diameter of 14 mm to obtain the positive electrode material.

[0034] When assembling CR2025 batteries, lithium sheets were used as negative electrodes, polypropylene film (Celgard 2400) was used as separators, CNT-S / ZIF-8@Hb was used as positive electrodes, and 1 wt% lithium nitrate (LiNO 3 ), 1M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in 1,3-dioxolane (DOL) and 1,2-dimethoxyethane (DME) (1:1, v / v), with a volume of about 25 μL mg −1The entire battery assembly was carried out inside a glove box and the water and oxygen levels were kept below 0.1 ppm. The assembled battery was then left to stand at room temperature for 12 h before testing. Electrochemical characterization was performed using a CHI 760E workstation with cyclic voltammetry (CV) testing ranging from 1.6 V to 2.8 V with an initial scan rate of 0.1 mV s −1 , for different scan rates, the rate is 0.2 mV s −1 To 0.5 mV s −1 Electrochemical impedance spectroscopy (EIS) tests were performed in a wide frequency range from 100kHz to 0.01Hz.

[0035] 1.4 Experimental methods (1) Li 2 S 6 Adsorption test First, in a glove box, Li 2 Then, a 0.2 M Li 2 S 6 The mixture was vigorously stirred at 60 °C for 24 h to ensure complete formation of Li 2 S 6 In the adsorption experiment, 2 mL of the prepared 0.2 M Li 2 S 6 The solution was transferred to a 3 mL sealed glass bottle, which remained within the confines of the glove box. ZIF-8@Hb (10 mg) and ZIF-8 (10 mg) were added to the glass bottle. The color change of the solution was recorded, and static adsorption images were taken at different times.

[0036] (2) Li 2 S deposition test The cathode used CNT / ZIF-8@Hb, CNT / ZIF-8 or CNT, and 10 µL of the prepared 0.2 MLi was injected into the cathode side. 2 S 6 The electrolyte solution is composed of 1.0 M LiTFSI and 1.0 wt% LiNO 3 composition, dissolved in a mixture of dimethyl ether and dichloroethane (1:1, v / v). 2 S deposition, on a battery test cabinet, was initially discharged at a constant current of 0.785 mA to 2.06 V, and then maintained at a constant potential discharge of 2.04 V until the discharge current dropped to 10 −5 A or below.

[0037] (3) GITT test The constant current intermittent titration technique (GITT) was tested on the Xinwei battery cabinet with a constant current pulse of 0.08 C for 7.5 minutes to stabilize the voltage, followed by a 75-minute rest to approach the open circuit voltage.

[0038] (4) In-situ UV-visible absorption spectroscopy test A Pt wire was used as the counter electrode, while a sealed Ag / AgCl cell was used as the reference electrode. The working electrode consisted of a glassy carbon electrode (diameter: 5 mm) coated with about 1 mg ZIF-8@Hb and 9 mg CNT composites. The three-electrode system was operated at 1.6 to 2.8 V (vs. Li / Li + ) with a scan rate of 0.3 mV s −1 Meanwhile, UV-visible absorption spectra were recorded at each voltage increment of 0.1 V using UV-visible spectrophotometry.

[0039] Experimental Results 1. Synthesis and characterization of ZIF-8@Hb composites The applicant synthesized the ZIF-8@Hb composite material by a simple room temperature aqueous solution reaction. Compared with the white ZIF-8 and the brown-red Hb, the light brown ZIF-8@Hb indicated that ZIF-8 and Hb were successfully integrated ( Figure 1 ).

[0040] The microstructure and composition of the catalyst were analyzed by scanning electron microscopy (SEM), X-ray powder diffractometer (XRD), Fourier transform infrared spectrometer (FT-IR) and X-ray photoelectron spectroscopy (XPS). Figure 2 ), the prepared ZIF-8 material has a regular rhombic dodecahedron appearance with clear edges, the average size of the material is about 400 nm, and the structure of the prepared ZIF-8@Hb composite material has not changed significantly. The XRD spectra of ZIF-8 and ZIF-8@Hb are shown in ( Figure 3 In (a), within the scanning diffraction angle range of 8~40°, a series of main diffraction peaks at 10.43°, 12.79°, 14.81°, 16.49° and 18.09° can be identified in the XRD spectrum of ZIF-8, and the five main signals are (002), (112), (022), (013) and (222), respectively, confirming the successful synthesis of high-crystalline ZIF-8. In the XRD spectrum of ZIF-8@Hb, the diffraction peaks are similar to those of ZIF-8, indicating that it maintains a good crystal structure, and these signals with weakened intensity can be monitored in the ZIF-8@Hb spectrum. As shown in the figure ( Figure 3b) shows the FTIR spectra of Hb, ZIF-8, and ZIF-8@Hb, respectively. In ZIF-8, the −1 、756 cm −1 、1573 cm −1 and 2932 cm −1 These signals are attributed to the presence of Zn-N, Zn-O, C=N (stretching vibration), and CH (stretching vibration), respectively. Amide bonds are common chemical bonds in biomacromolecules such as proteins and peptides, and the 1640 cm-1 molecule was observed in the spectra of both Hb and ZIF-8@Hb composites. −1 The C=O stretching vibration in the amide bond at the end of the ZIF-8 bond confirms the successful internalization of Hb into ZIF-8. The only difference between the two is that after Hb is integrated into ZIF-8, the spectral absorption peak of the amide II band undergoes a red shift to a lower wave number (from 1645 cm −1 Move to 1641 cm −1 ). A common sharp peak was found in the UV-visible spectrum of the material at 200 nm. This signal is related to the π-π* electronic transition within the aromatic ring of these systems. Hb and ZIF-8@Hb showed the same peaks at 277 nm and 405 nm, which were attributed to the π-π* electronic transition within the porphyrin unit of Hb and the dd electronic transition of the Fe-porphyrin complex. The similar UV-visible absorption of ZIF-8@Hb and Hb indicated the presence of complete Hb in ZIF-8. These results indicate that despite the hydrogen bonding interaction between Hb and ZIF-8, the successful attachment of Hb molecules to the MOF material and the inherent structure of the heme site in Hb are basically maintained, a conclusion consistent with the results of FTIR experimental analysis. Characteristic peaks of Zn 2p, O 1s, C 1s, S 2p and Fe 2p were observed in the full XPS spectrum of the ZIF-8@Hb composite. The XPS spectrum of Zn 2p has two peaks at 1021.7 and 1044.9 eV, corresponding to Zn 2p 1 / 2 and Zn 2p 3 / 2 The C 1s spectrum can be divided into three peaks: C=O (287.8 eV), CO / CS (286.0 eV), and CC / C=C (284.8 eV). In the O 1s spectrum, the three peaks at 533.2, 532.5, and 531.7 eV are related to CO, SO, and C=O, respectively. These results confirm that Zn 2+ The coordination with organic ligands formed ZIF-8 crystals. The three peaks of S 2p spectrum at 165.4, 164.2 and 162.7 eV are respectively related to S 2p 1 / 2 、S 2p 3 / 2 In the Fe 2p spectrum, it is confirmed that Fe2+ and Fe 3+ When the iron in Hb is in the state of ferrous ions, it can react reversibly with oxygen and has oxygen-carrying capacity. Therefore, ZIF-8@Hb can react with the active substance S to promote the conversion of polysulfides. 2. Electrochemical performance of lean electrolyte By adjusting the proportion of ZIF-8@Hb, the optimal mass ratio of ZIF-8@Hb catalyst in the electrode was determined to be 0.5wt% ( Figure 4 To measure the fast charging characteristics, the discharge specific capacities of CNT, ZIF-8, and ZIF-8@Hb batteries were measured at different current densities ( Figure 5 b, c, Figure 6 ) and voltage-capacity curve ( Figure 7 ). ZIF-8@Hb exhibited the highest discharge capacity at all tested currents, demonstrating excellent performance. At 0.2, 0.5, 1.0, 2.0, 3.0 C, and 5.0 C rates (based on the mass of sulfur, 1 C = 1675 mAh g −1 )( Figure 5 In (a), the discharge capacities are as high as 1525.2, 1046.2, 889.5, 787.4 and 693.5 mAh g −1 , which outperforms the ZIF-8 battery (1438.3, 979.7, 844.7, 725.5, 667.7, and 585.9 mAh g −1 ) and CNT batteries (1142.8, 812.4, 741.1, 639.3, 575.8, and 353.3 mAh g −1 ), when the rate is switched back to 0.2 C, it is comparable to the ZIF-8 battery (918.7 mAh g −1 ) and CNT batteries (787.7 mAh g −1 ), the ZIF-8@Hb battery can recover 971.5 mAh g −1 The reversible capacity of ZIF-8@Hb indicates that the catalyst has excellent electrochemical reversibility. The high catalytic activity of ZIF-8@Hb leads to low voltage polarization, which is confirmed by the voltage difference of the charge-discharge platform from 0.2 C to 5.0 C. Therefore, the ZIF-8@Hb cathode shows good long-term cyclability with an initial capacity of 907.6 mAh g at 3.0 C. −1 After 500 cycles, it can still maintain about 423.9 mAh g −1 , the capacity decay is low, decaying by 0.106% per cycle, which is much better than CNT and ZIF-8 batteries ( Figure 8 ).

[0041] Sulfur content, E / S ratio, and sulfur loading are key factors for expanding the practical application of lithium-sulfur batteries. To further evaluate the performance of electrodes with ZIF-8@Hb catalysts under harsh working conditions, the applicant assembled a sulfur loading of 5.0 mg cm −2 The battery, and in 5 μL mg −1 The evaluation was conducted under lean electrolyte conditions. Figure 5 As shown in middle d, the ZIF-8@Hb battery shows 986.3 mAh g at 0.1 C. −1 The initial discharge capacity of the battery can still be maintained at 672.5 mAh g after 100 cycles. −1 The capacity of the battery is 200W, and the capacity decay per cycle is low, only 0.32%. Figure 5 As shown in Figure e, when the rate is increased to 0.2 C, the initial capacity is 818.6 mAh g −1 After 80 cycles, it gradually stabilized at 609.2 mAh g −1 , indicating that ZIF-8@Hb plays a key role in accelerating sulfur redox kinetics under practical conditions.

[0042] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. Application of ZIF-8 encapsulated hemoglobin composite materials in the preparation of lithium-sulfur batteries.

2. The use according to claim 1, characterized in that: The ZIF-8 wrapped hemoglobin composite material is prepared by the following method: firstly, a 2-methylimidazole methanol solution is mixed with a hemoglobin aqueous solution to obtain a mixed solution, then a zinc nitrate methanol solution is added to the mixed solution, ultrasonic oscillation treatment is performed, stirring is performed at room temperature, centrifugation is performed to obtain a precipitate, washing is performed, and drying is performed.

3. The use according to claim 2, characterized in that: The volume ratio of 2-methylimidazole methanol solution, hemoglobin aqueous solution, and zinc nitrate methanol solution is 9:1:10, the concentration of 2-methylimidazole methanol solution is 0.030-0.040 g / mL, the concentration of hemoglobin aqueous solution is 55-65 mg / mL, and the concentration of zinc nitrate methanol solution is 0.025-0.03 g / mL.

4. The use according to claim 2, characterized in that: The process conditions of ultrasonic oscillation treatment are: 500W ultrasonic oscillation for 30 minutes.

5. The use according to claim 2, characterized in that: The process conditions of stirring at room temperature are: stirring at 600 r / min for 24 hours.

6. The use according to claim 2, characterized in that: The centrifugal process conditions are: 8000r / min for 3min, and 5 times of centrifugation.

7. The use according to claim 2, characterized in that: The mixture was washed with methanol three times until the supernatant was clear and colorless.

8. The use according to claim 2, characterized in that: The drying process conditions are: drying at 60°C for 12 hours.

Citation Information

Patent Citations

  • Method for preparing self-doped Fe-N-C oxygen reduction electrocatalyst through animal blood salting-out thermal polymerization

    CN108855179A

  • Preparation method of G-quadruplex / heme enzyme / carbon nanotube composite and application of G-quadruplex / heme enzyme / carbon nanotube composite to lithium-sulfur battery

    CN109742338A

  • Method for guiding efficient and universal enzyme wrapping through seed crystal and application of efficient and universal enzyme wrapping method

    CN115536751A

  • Catalytic site, positive electrode active material and lithium-sulfur battery comprising the same

    KR1020180133063A

  • Particles comprising proteins encapsulated in a porous framework and methods of using thereof

    WO2023196306A1

Cited By

  • Preparation process of ZIF-8 / Hb mixed LB film

    CN121045601A

  • A preparation process for ZIF-8 / Hb hybrid LB films

    CN121045601B